Emotion and the Psychological Distance of Climate Change. Issue 6 (December 2019) - Chu, Haoran; Yang, Janet Z.
Anchored by construal level theory and appraisal theories of emotion, this study examines whether discrete emotions vary along with perceived psychological distance of climate change impacts. We found that reduced psychological distance perception led to an increase in concrete emotions such as anger, fear, sadness, and guilt. In contrast, increased psychological distance perception led to an increase in hope—an abstract emotion. Compared to anger, anxiety, and hope, fear, guilt, and shame had more limited impact on climate mitigation action and policy support. Trait empathy moderated the effect of psychological distance manipulation on distance perception and emotions.